The Educational Environment According to the Qur'an and Hadith: Perspectives and Implications: (Integrasi Sanad dalam Penafsiran Kontekstual Al-Qur’an: Sebuah Perspektif Berbasis Maqasid) - Inayah, Inayah; Ali, Moh; Hidayat, Ade; Yuniartin, Titin (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Sekolah Tinggi Ilmu Al-Qur'an Al Multazam Kuningan, 2025)
The educational environment in Islam plays a strategic role in shaping students' character. This study aims to explore the concept of the academic environment from the perspective of the Qur'an and Hadith and analyze its implications for the formation of an Islamic generation. Employing a qualitative approach with a literature review method, the research examines various relevant sources. The findings identify three main dimensions of an ideal educational environment: the family, school, and community. These three dimensions are interdependent and work synergistically to shape a generation rooted in faith, knowledge, and noble character. The family serves as the initial foundation for instilling values of faith and morality. The school extends this foundation through structured, formal education, and the community provides a real-life context for practicing these values. This study highlights the lack of integration between family, school, and community roles in current Islamic educational models. It concludes that strengthening the synergy among these three pillars can contribute significantly to building a holistic Islamic education system that is adaptive to contemporary challenges and capable of fostering character education based on Islamic values.